High-solid-content low-viscosity polyamide acid slurry as well as preparation method and application thereof
By using phthalene compounds as the capping agent in the preparation of polyamic acid slurry, imidation and chain growth are completed, and the problems of low solid content and high viscosity of polyamic acid slurry are solved, achieving high efficiency Spray processing and excellent performance polyimide coating.
Patent Information
- Application Number
- CN202411730054.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
AI Technical Summary
The solid content of existing polyamic acid slurries is low and the viscosity is high, making it difficult to meet the requirements of spraying processing, and conventional methods will affect the performance of polyimide in the process of reducing viscosity.
Phthalonitrile compounds are used as the capping agent, and imidation and chain growth are completed through high-temperature links in the polycondensation reaction of diamine and dianhydride, and a high-solid, low-viscosity polyamic acid slurry is achieved.
The obtained polyamic acid slurry has high solid content and low viscosity, which is suitable for spraying and processing, improves processing efficiency and product yield, and does not affect the mechanical, thermodynamic and insulating properties of the polyimide.
Smart Images

Figure BDA0005162239650000041 
Figure BDA0005162239650000101 
Figure BDA0005162239650000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of slurries, and in particular relates to a polyamic acid slurry with high solid content and low viscosity, and a preparation method and application thereof. Background Art
[0002] Spraying is one of the most common processing methods in the coating industry. It not only has high processing efficiency and can realize streamlined operation, but also can effectively guarantee processing precision. However, spraying has extremely stringent requirements on the viscosity and solid content of coatings or paints. If the viscosity is too high, spraying is difficult to achieve, especially the spraying accuracy and continuity are difficult to guarantee. Therefore, the conventional coating spraying viscosity is generally controlled below 2500cp / 25℃; at the same time, when processing thicker film layers, the requirements for the solid content of the coating are higher. If the solid content is too low, the spraying process requires more passes and the thickness uniformity is difficult to guarantee, especially for the spraying process of different components.
[0003] Polyimide (PI) has been widely used due to its excellent heat resistance, excellent insulation performance, good mechanical properties, excellent chemical stability, moisture resistance and radiation resistance. Because of the chemical stability of polyimide, polyimide is difficult to dissolve and melt, so it is determined that the product can only be used by thermal curing molding, and then cut and bonded. Especially for some new energy vehicles, inverters and other equipment that need to be insulated and have high temperature resistance, the current conventional practice is to coat the polyimide film with glue and cut it into the required shape and then manually bond it; however, this method is not only complicated in process flow and difficult to achieve streamlined production, but also has low processing yield. The main reason is that the current polyamic acid slurry has a low solid content and a high viscosity. The viscosity is generally 8-50wcp / 25℃, and the solid content is 13-20%. Even if the polyamic acid slurry is diluted to achieve a low viscosity spraying solution, the solid content of the diluted slurry is extremely low, the spraying passes are many and the uniformity is poor, and the cost performance is not high. Therefore, in order to provide a polyamic acid slurry that can be processed by spraying, the problems of viscosity and solid content must be solved, that is, low viscosity and high solid content.
[0004] For example, the methods disclosed in CN104292459A and CN112708133A both control the viscosity by adding a capping agent to reduce the degree of polymerization of polyamic acid. However, this invention will affect the properties of the polyimide itself, resulting in a decrease in the mechanical properties or thermodynamic properties of the final polyimide film.
[0005] For another example, CN103788651A discloses a method for reacting the carboxyl groups in polyamic acid to effectively reduce the viscosity of the polyamic acid; however, the methylchlorosilane added in this method not only reduces the thermodynamic and mechanical properties of the film during the imidization process, but also produces HCl during thermal decomposition during the heating process, which corrodes instruments or equipment.
[0006] For another example, the methods disclosed in CN111808285A and CN117050304A both use the method of adding water or alcohol to the reaction system to hydrolyze or esterify the acid anhydride to reduce the viscosity of the polyamic acid; however, the dianhydride needs to react with water or alcohol first, and then the diamine is added, and the water content of the solvent is very strict, otherwise the batch stability is difficult to guarantee.
[0007] In summary, it can be seen that although there are some methods in the prior art that can effectively realize the preparation of high-solid content and low-viscosity polyamic acid slurry, these existing methods still have some problems, such as reducing the mechanical properties or thermodynamic properties after film formation, or having very stringent requirements on the water content of the reaction solvent, or poor batch stability of the product.
[0008] Therefore, in order to solve the above problems, it is urgent to develop a polyamic acid slurry that has both high solid content and low viscosity, and the polyimide film still has excellent mechanical properties, thermal stability and insulation after curing. Summary of the invention
[0009] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-solid-content, low-viscosity polyamic acid slurry and a preparation method and application thereof. The polyamic acid slurry has both high solid content and low viscosity, and has excellent storage stability, is suitable for spray processing technology, can effectively improve processing efficiency and product yield, and at the same time, the polyimide coating formed after spraying and imidization also has excellent mechanical properties, thermodynamic properties and insulation properties, and is suitable for use in new energy vehicles, inverters and other equipment.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a high-solid-content, low-viscosity polyamic acid slurry, wherein the raw materials for preparing the polyamic acid slurry include diamine, dianhydride, a capping agent and an organic solvent;
[0012] The end-capping agent includes phthalonitrile compounds.
[0013] Phthalonitrile compounds are a class of compounds in which the hydrogen on the adjacent carbon of the benzene ring is replaced by a cyano group. These compounds are in a stable state at relatively low temperatures (e.g., ≤100°C), but at high temperatures, especially under the catalysis of amines, they can further react to increase the molecular weight of the polymer.
[0014] Based on the above content, the inventors of the present invention creatively discovered during the research process: in the process of polycondensation reaction of diamine and dianhydride in an organic solvent, phthalonitrile compounds are used as end-capping agents for the polycondensation reaction. Taking advantage of their stability at room temperature and reaction activity at high temperature, after the polyamic acid slurry is prepared, in the subsequent solid-containing film-forming process, the chain growth of the polymer can be achieved while completing the ring-closing imidization during the high-temperature link. Therefore, adding phthalonitrile compounds as end-capping agents can effectively increase the solid content of the polyamic acid slurry and reduce the viscosity of the polyamic acid slurry.
[0015] The present invention provides a polyamic acid slurry with high solid content and low viscosity by using the above-mentioned raw materials for preparation, so that it is suitable for the spraying process, and can effectively reduce the number of coating passes when preparing the polyimide coating, greatly improving the production capacity. At the same time, the polyimide coating obtained by the method will not reduce the excellent mechanical properties, thermodynamic properties and insulation properties of the polyimide itself; in addition, compared with traditional polyamic acid, less organic solvent evaporates during curing at the same viscosity, so the number of spraying times can be reduced, the production capacity can be improved, and the energy consumption can be further reduced to save more energy; compared with the traditional film-sticking process, the error caused by human factors that leads to a decrease in product yield is greatly reduced.
[0016] Preferably, the polyamic acid slurry is obtained by using a phthalonitrile compound as a capping agent and subjecting a dianhydride and a diamine to a polycondensation reaction in a solvent.
[0017] Preferably, the solid content of the polyamic acid slurry is 16-33%, for example, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32% or 33%, and further 20-28%, and the viscosity of the polyamic acid slurry corresponding to the solid content is 200-5000cp / 25°C, for example, 200cp / 25°C, 500cp / 25°C, 1000cp / 25°C, 1500cp / 25°C, 2000cp / 25°C, 2500cp / 25°C, 3000cp / 25°C, 3500cp / 25°C, 4000cp / 25°C, 4500cp / 25°C or 5000cp / 25°C, and further preferably 200-2500cp / 25°C. In addition, the polyamic acid slurry provided by the present invention has both high solid content and low viscosity, and the amount of the end-capping agent can be reasonably adjusted according to the solid content to obtain the corresponding viscosity.
[0018] Preferably, the molar ratio of the end-capping agent to the diamine is (0.2-6):10, such as 0.2:10, 0.5:10, 1:10, 1.5:10, 2:10, 2.5:10, 3:10, 3.5:10, 4:10, 4.5:10, 5:10, 5.5:10 or 6:10, etc. If the amount of the end-capping agent is too low, the viscosity of the obtained polyamic acid slurry will be too high, and it will be difficult to achieve high solid content and low viscosity; and if the amount of the end-capping agent is too high, although a polyamic acid slurry with high solid content and low viscosity can be obtained, the continuity and mechanical properties of the obtained polyimide coating after subsequent imidization film formation will be reduced.
[0019] Preferably, the phthalonitrile compound has a structure as shown in the following formula I:
[0020]
[0021] In Formula I, represents any one of an aryl group or a heteroaryl group, for example, phenyl, naphthyl, anthracenyl, phenoxy, etc. can be selected.
[0022] Preferably, the phthalonitrile compound includes any one of 4-aminophthalonitrile, 4-(4-aminophenoxy)phthalonitrile or 6-amino-2,3-dicyanonaphthalene or a combination of at least two thereof.
[0023] Preferably, the molar ratio of the dianhydride to the diamine is (1.01-1.3):1, for example, 1.01:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1 or 1.3:1, etc.
[0024] Preferably, the diamine is an aromatic diamine.
[0025] In the present invention, there is no particular limitation on the specific type of the aromatic diamine, and any existing aromatic diamine that can be used to prepare polyamic acid can be used.
[0026] Exemplarily, the aromatic diamine includes any one of p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4'-diaminobenzanilide, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, 4,4'-diaminodiphenyl sulfone, 2-(4-aminophenyl)-5-aminobenzimidazole, 2,2-bis(4-hydroxy-3-aminophenyl)propane, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl, 4,4'-diamino-biphenyl or 9,9-bis(4-aminophenyl)fluorene, or a combination of at least two thereof.
[0027] Preferably, the dianhydride is an aromatic dianhydride.
[0028] Likewise, in the present invention, there is no particular limitation on the specific type of the aromatic dianhydride, and any existing aromatic dianhydride that can be used to prepare polyamic acid can be used, for example, aromatic tetracarboxylic dianhydride can be selected.
[0029] For example, the aromatic tetracarboxylic dianhydride includes 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 1,2,4,5-pyromellitic dianhydride, (4-phthalic anhydride) formyloxy-4-phthalate, bis[(3,4-dianhydride)phenyl]terephthalate, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, p- Any one of phenylene-diphthalate dianhydride, 4,4'-phenylenedioxydiphthalic anhydride, pyromellitic tetracarboxylic anhydride, 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride, 2,2-bis(4-(3,4-dicarboxyphenoxy)phenyl)hexafluoropropane dianhydride, 2,2-bis(4-(3,4-dicarboxybenzoyloxy)phenyl)hexafluoropropane dianhydride or 2,2'-bis(trifluoromethyl)-4,4'-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride or a combination of at least two thereof.
[0030] Preferably, the organic solvent includes any one or a combination of at least two of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP) or γ-butyrolactone.
[0031] In a second aspect, the present invention provides a method for preparing a high-solid-content, low-viscosity polyamic acid slurry as described in the first aspect, the preparation method comprising: first adding a diamine and a capping agent into an organic solvent for mixing, and then adding a dianhydride for polycondensation reaction to obtain the polyamic acid slurry.
[0032] Preferably, the mixing temperature is 30-80°C, for example, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, and more preferably 40-70°C.
[0033] Preferably, the mixing time is 1 to 5 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, and more preferably 2 to 4 hours.
[0034] Preferably, the temperature of the polycondensation reaction is 30-80°C, for example, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, and more preferably 40-70°C.
[0035] Preferably, the polycondensation reaction time is 3 to 15 h, for example, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h.
[0036] In a third aspect, the present invention provides a polyimide coating, which is obtained by spraying the high-solid-content, low-viscosity polyamic acid slurry as described in the first aspect onto a substrate, and then heating to remove the solvent and simultaneously complete imidization and chain extension.
[0037] In the present invention, there is no special restriction on the temperature of the imidization. In principle, it can be any temperature not exceeding the decomposition temperature of the polyamic acid. However, in order to ensure that the imidization is more complete and the physical and chemical properties of the formed polyimide coating are better, the temperature of the imidization is further limited to 300-450°C, for example, 450°C, 400°C, 350°C or 300°C.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The polyamic acid slurry provided by the present invention has both high solid content and low viscosity, and has long-term room temperature storage stability, which is beneficial to the casting stability during spraying processing;
[0040] (2) The polyamic acid slurry provided by the present invention can effectively reduce the number of coating passes and significantly increase production capacity. At the same time, the coating obtained by this method will not reduce the excellent mechanical properties, thermodynamic properties and insulation properties of the polyimide itself;
[0041] (3) The polyamic acid slurry provided by the present invention uses less solvent, and the amount of evaporated solvent during imidization to prepare the coating is small, which can reduce energy consumption and production costs;
[0042] (4) The polyamic acid slurry provided by the present invention is suitable for spraying technology, and can also solve the cumbersome process of manual film pasting, especially solve the problem of complex graphics, greatly improving the yield of finished products. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0044] Example 1
[0045] A high solid content and low viscosity polyamic acid slurry, with a solid content of 25.2% and a viscosity of 1896cp / 25°C;
[0046] The preparation method of the high-solid-content and low-viscosity polyamic acid slurry provided in this embodiment includes: adding 2602g of DMAc to a 5L reactor, then adding 400.48g of 4,4'-diaminodiphenyl ether (ODA), adding 17.538g of 4-aminophthalonitrile under stirring, heating to 50°C and stirring for 2h; then adding 449.32g of 1,2,4,5-pyromellitic dianhydride (PMDA) to the reactor in batches, maintaining the system temperature at 50°C, reacting for 8h, and obtaining the high-solid-content and low-viscosity polyamic acid slurry.
[0047] Example 2
[0048] A high solid content and low viscosity polyamic acid slurry, with a solid content of 28.3% and a viscosity of 2003cp / 25°C;
[0049] The preparation method of the high-solid content and low-viscosity polyamic acid slurry provided in this embodiment includes: adding 2281g of DMAc to a 5L reactor, then adding 400.48g of ODA, adding 28.63g of 4-aminophthalonitrile under stirring, heating to 50°C and stirring for 2h; then adding 458.052g of PMDA to the reactor in batches, maintaining the system temperature at 50°C, reacting for 8h, and obtaining the high-solid content and low-viscosity polyamic acid slurry.
[0050] Example 3
[0051] A high solid content and low viscosity polyamic acid slurry, with a solid content of 27.4% and a viscosity of 1650cp / 25°C;
[0052] The preparation method of the high-solid-content, low-viscosity polyamic acid slurry provided in this embodiment is different from that in Example 1 in that 28.23 g of 4-(4-aminophenoxy)phthalonitrile is used to replace 17.538 g of 4-aminophthalonitrile; other substances, amounts and steps are the same as those in Example 1.
[0053] Example 4
[0054] A high solid content and low viscosity polyamic acid slurry, with a solid content of 26.7% and a viscosity of 1760cp / 25°C;
[0055] The preparation method of the high-solid-content, low-viscosity polyamic acid slurry provided in this embodiment is different from that in Example 1 in that 23.18 g of 6-amino-2,3-dicyanonaphthalene is used to replace 17.538 g of 4-aminophthalonitrile; other substances, amounts and steps are the same as those in Example 1.
[0056] Example 5
[0057] A high solid content and low viscosity polyamic acid slurry, with a solid content of 13.5% and a viscosity of 2032cp / 25°C;
[0058] The preparation method of the high-solid-content and low-viscosity polyamic acid slurry provided in this embodiment is different from that in Example 1 in that: the amount of 4-aminophthalonitrile used is 5.726 g; other substances, amounts and steps are the same as those in Example 1.
[0059] Example 6
[0060] A high solid content and low viscosity polyamic acid slurry, with a solid content of 29.2% and a viscosity of 345cp / 25°C;
[0061] The method for preparing the high-solid-content, low-viscosity polyamic acid slurry provided in this embodiment is different from that in Example 1 in that: the amount of 4-aminophthalonitrile used is 214.718 g; other substances, amounts and steps are the same as those in Example 1.
[0062] Comparative Example 1
[0063] A polyamic acid slurry having a solid content of 23.8% and a viscosity of 2450cp / 25°C;
[0064] The preparation method of the polyamic acid slurry provided in this comparative example includes: adding 2602g of DMAc to a 5L reactor, then adding 400.48g of ODA, heating to 50°C and stirring for 2h; then adding 449.32g of PMDA to the reactor in batches, maintaining the system temperature at 50°C, reacting for 8h, and obtaining the polyamic acid slurry.
[0065] Comparative Example 2
[0066] A polyamic acid slurry having a solid content of 5% and a viscosity of 1508cp / 25°C;
[0067] The preparation method of the polyamic acid slurry provided in this comparative example includes: adding 15890g of DMAc to a 5L reactor, then adding 400.48g of ODA, heating to 50°C and stirring for 2h; then adding 436.24g of PMDA to the reactor in batches, maintaining the system temperature at 50°C, reacting for 8h, and obtaining the polyamic acid slurry.
[0068] Application Example 1
[0069] A polyimide coating, the preparation method of which comprises: transferring the high-solid-content, low-viscosity polyamic acid slurry provided in Example 1 into a spray chamber, controlling the spraying amount by adjusting the pressure, spraying the slurry evenly onto the surface of the sample, transferring the sample to a 150°C oven and baking it for 5 minutes after each spraying for 30 seconds, spraying again, repeating 3 times, and then heating the oven to 450°C, removing the solvent and completing imidization and chain extension to obtain the polyimide coating.
[0070] Application Examples 2 to 6 and Comparative Application Examples 1 to 2
[0071] A polyimide coating is disclosed, which differs from Application Example 1 in that the polyamic acid slurries provided in Examples 2 to 6 and Comparative Examples 1 to 2 are used to replace the polyamic acid slurry provided in Example 1, and other steps, conditions and parameters are the same as those in Application Example 1.
[0072] (1) Performance test of slurry:
[0073] ① Solid content: Take an aluminum foil plate with a diameter of 60 mm and weigh it as m0; take 1±0.1g of slurry sample and place it in the aluminum foil plate, weigh the weight of the aluminum foil plate plus the slurry as m1; put the aluminum foil plate containing the slurry in a blast oven, dry it at 180±5℃ for 1h, then take it out and weigh the mass of the aluminum foil plate containing the slurry as m2; then the solid content = (m2-m0) / (m1-m0)×100%.
[0074] ②Viscosity: Use American Boller cone and plate viscometer to test the viscosity of the slurry at 25°C.
[0075] ③Appearance: visual observation.
[0076] ④ Storage stability: After being placed at room temperature for 30 days, observe whether the slurry is uniform and whether there is stratification.
[0077] The polyamic acid slurries provided in Examples 1 to 6 and Comparative Examples 1 to 2 were tested according to the above test method. The test results are shown in Table 1:
[0078] Table 1
[0079]
[0080]
[0081] From the data in Table 1, we can see that:
[0082] The polyamic acid slurries provided in Examples 1 to 6 have both high solid content and low viscosity. The slurries all appear as brown-yellow transparent liquids, and no stratification occurs after being placed at room temperature for 30 days, indicating good storage stability. In particular, the polyamic acid slurries provided in Examples 1 to 4 have a solid content of up to 25.2 to 28.3%, and a viscosity of only 1650 to 2003 cp / 25°C.
[0083] Comparing the results of Example 1 and Comparative Example 1, it can be seen that no end-capping agent is added to the raw materials for preparing the polyamic acid slurry provided in Comparative Example 1, so the solid content is low and the viscosity is high, which is difficult to meet the requirements of the spraying process.
[0084] Comparing the results of Example 1 and Comparative Example 2, it can be seen that as the amount of solvent increases, the viscosity of the obtained polyamic acid slurry can be reduced, but the solid content will be reduced. At the same time, stratification will occur after being placed at room temperature for 30 days, and the storage stability will deteriorate.
[0085] (2) Performance test of polyimide coating
[0086] ①Thickness: Test according to GB / T4851.1-1998 insulation tape standard thickness method.
[0087] ② Breakdown voltage: refer to GB / T 7752-1987 Insulating adhesive tape power frequency breakdown strength test method.
[0088] ③ Adhesion: Test the initial adhesion and adhesion after boiling in accordance with the GB9286 100-grid test standard.
[0089] ④Continuity: Visually observe whether the coating is continuous.
[0090] The polyimide coatings provided in Examples 1 to 6 and Comparative Application Examples 1 to 2 were tested according to the above test method. The test results are shown in Table 2:
[0091] Table 2
[0092] Film thickness / μm Voltage / kV 100 grid test Boiling test Film continuity Application Example 1 44 7.8 5B 5B continuous Application Example 2 56 8.5 5B 5B continuous Application Example 3 51 8.4 5B 5B continuous Application Example 4 46 8.4 5B 5B continuous Application Example 5 22 5.2 5B 5B continuous Application Example 6 68 9.3 5B 2B Discontinuous Comparative application example 1 40 6.5 B 0B Discontinuous Comparative Application Example 2 12 3.5 5B 3B continuous
[0093] From the data in Table 2, we can see that:
[0094] The polyimide coatings provided in Application Examples 1 to 5 have excellent mechanical properties, thermodynamic properties and insulation properties, and the coatings have good continuity and no cracking, indicating that the spraying is very uniform; in particular, the polyimide coatings provided in Application Examples 1 to 4 have a thickness of up to 44 to 56 μm, a breakdown voltage of up to 5.2 to 8.5 kV, and both the initial adhesion and the adhesion after boiling can reach 5B.
[0095] From the data of Comparative Application Example 1 and Comparative Application Example 1, it can be seen that the polyimide coating provided in Comparative Application Example 1 is relatively thin, has poor continuity, and has cracking problems. At the same time, the breakdown voltage is low, the initial adhesion and adhesion after boiling are low, and the mechanical properties, thermodynamic properties and insulation properties are poor.
[0096] Comparing the data of Application Example 1 and Comparative Application Example 2, it can be seen that the thickness of the polyimide coating provided in Comparative Application Example 2 is extremely low, only 12 μm, and the breakdown voltage is low and the insulation performance is poor.
[0097] Finally, by comparing the data of Application Example 1 and Application Example 6, it can be seen that the polyimide coating provided by Application Example 6 also has the problem of discontinuity. This is because too much is added, and the overall molecular weight of the effective polyamic acid is low. Although phthalonitrile can continue to react by heating, the amount of solvent is reduced or even solvent-free during the curing process, the chance of molecular chain collision is reduced, and the chain growth is relatively limited, resulting in a small molecular weight. In addition, the film thickness is too thick, so cracks occur.
[0098] The applicant declares that the present invention illustrates a high-solid-content, low-viscosity polyamic acid slurry and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A high solid content and low viscosity polyamic acid slurry, characterized in that: The raw materials for preparing the polyamic acid slurry include diamine, dianhydride, end-capping agent and organic solvent; The end-capping agent includes phthalonitrile compounds.
2. The polyamic acid slurry according to claim 1, characterized in that The polyamic acid slurry is obtained by using phthalonitrile compounds as end-capping agents and subjecting dianhydride and diamine to polycondensation reaction in an organic solvent.
3. The polyamic acid slurry according to claim 1 or 2, characterized in that: The polyamic acid slurry has a solid content of 16-33% and a viscosity of 200-5000cp / 25°C; Preferably, the polyamic acid slurry has a solid content of 20-28% and a viscosity of 200-2500 cp / 25°C.
4. The polyamic acid slurry according to any one of claims 1 to 3, characterized in that The molar ratio of the end-capping agent to the diamine is (0.2-6):10; Preferably, the phthalonitrile compound has a structure as shown in the following formula I: In Formula I, represents any one of an aryl group or a heteroaryl group; Preferably, the phthalonitrile compound includes any one of 4-aminophthalonitrile, 4-(4-aminophenoxy)phthalonitrile or 6-amino-2,3-dicyanonaphthalene or a combination of at least two thereof.
5. The polyamic acid slurry according to any one of claims 1 to 4, characterized in that: The molar ratio of the dianhydride to the diamine is (1.01-1.3):1; Preferably, the diamine is an aromatic diamine; Preferably, the dianhydride is an aromatic dianhydride.
6. The polyamic acid slurry according to any one of claims 1 to 5, characterized in that: The organic solvent includes any one of N,N-dimethylformamide, dimethyl sulfoxide, N-dimethylacetamide, N-methylpyrrolidone or γ-butyrolactone, or a combination of at least two thereof.
7. A method for preparing a high solid content and low viscosity polyamic acid slurry according to any one of claims 1 to 6, characterized in that: The preparation method comprises: firstly adding diamine and end-capping agent into an organic solvent for mixing, and then adding dianhydride for polycondensation reaction to obtain the polyamic acid slurry.
8. The preparation method according to claim 7, characterized in that: The mixing temperature is 30 to 80°C, preferably 40 to 70°C; Preferably, the mixing time is 1 to 5 hours, more preferably 2 to 4 hours.
9. The preparation method according to claim 7 or 8, characterized in that: The temperature of the polycondensation reaction is 30 to 80°C, more preferably 40 to 70°C; Preferably, the polycondensation reaction time is 3 to 15 hours.
10. A polyimide coating, characterized in that: The polyimide coating is obtained by spraying the high-solid-content, low-viscosity polyamic acid slurry as claimed in any one of claims 1 to 6 onto a substrate, and then heating to remove the organic solvent and simultaneously complete imidization and chain extension.
Citation Information
Patent Citations
Low-apparent-viscosity polyamide acid solution and preparation method thereof
CN103788651A
Preparation method of high-solid-content and low-viscosity polyimide material
CN104292459A
Method for preparing polyamide acid composition with low viscosity and controllable solid content
CN111808285A
Low-viscosity thermosetting polyimide resin as well as preparation method and application thereof
CN112708133A
Low-viscosity high-solid-content polyamide acid slurry as well as preparation method and application thereof
CN117050304A